A lightweight authentication and key exchange mechanism for IPv6 over low‐power wireless personal area networks‐based Internet of things. Issue 5 (11th August 2020) - Chom Thungon, Leki; Ahmed, Nurzaman; Chandra Sahana, Subhas; Hussain, Md. Iftekhar
Abstract: The authentication mechanism in IPv6 over low‐power wireless personal area networks (6LoWPAN) uses media access control identifier and IPv6 address. The traditional wireless sensor network considers three‐factor authentication mechanism. These factors, namely, username, password, and biometric create a huge overhead in Internet of things due to resource‐constraint devices in terms of low memory and processing capabilities. In this article, we propose a lightweight key exchange and authentication scheme for 6LoWPAN to efficiently authenticate the resource‐constraint sensor devices. The proposed scheme uses hash‐based approaches in the setup and registration phase to reduce the computational cost and resource consumption overhead. The analytical results over the automated validation of internet security protocols and applications and ProVerif tools validate the security claim of the proposed scheme against threats like replay and man‐in‐the‐middle attack. Furthermore, we analyze the logic correctness of the proposed authentication scheme using Burrows‐Abadi‐Needham logic. Abstract : Architecture of proposed lightweight authentication scheme. In this paper, we analyzed the efficiency of existing authentication and key‐exchange mechanism for 6LoWPAN networks. We propose a symmetric key‐based approach to mutually authenticate the sensors, gateway and, the server. Our scheme uses hash‐based approaches for resource constraints devices to reduce the computation overhead. A brief description of the architecture of the proposed scheme is shown in the below Figure. Our scheme consists of a sensor node, gateway and, the server. A sensor node sends an authentication request to the gateway with its security credentials. The gateway verifies the node for its authenticity with its database and authenticates the node. The gateway forwards the request to the server to authenticate itself. Thus, achieving mutual authentication between the sensor node, gateway and, the server.